Sharia Microfinance and SME Growth: Evidence from PNM Mekaar Syariah Clients in Palopo City, Indonesia - Lisa lisawati; Nurfitraeny Nasruddin (Institut Agama Islam Negeri Palopo, 2025)
This research discusses the influence of sharia microfinancing on the development of Micro, Small and Medium Enterprises (MSMEs) among PNM Mekaar Syariah Bara Palopo City customers. Using a quantitative approach, this research involved 93 customers who had received loans at PNM Mekaar Syariah Bara Unit, Palopo City. The data collection procedure uses the Questionnaire and Observation method using linear regression analysis to identify the relationship between micro financing and the development of MSMEs, which is measured through indicators such as increasing business scale, level of business difficulty, capital characteristics, type of business, increasing sales turnover, and job creation. The research results show that sharia microfinancing has a significant positive influence on the development of MSMEs. These findings indicate the important role of sharia financial institutions in supporting the growth of the MSME sector, as well as providing recommendations for developing more effective policies and programs. Keywords: Sharia Microfinance, Increasing MSMEs, Customers.